THE RELATIONSHIP BETWEEN SHOPEE’S BRAND AWRANESS, BRAND ASSOCIATION AND PERCEIVED QUALITY TOWARDS SHOPEE’S CUSTOMER SATISFACTION AMONG INDONESIAN YOUNG-ADULTS - Jasmine Zahra; Triyono Lukmantoro; Primada Qurrota Ayun (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2022)
Due to their adaptability and the capacity of technology to integrate aspects of human life, technological advancements and developments, particularly in the fields of telecommunications, information, and multimedia, have a significant impact on adaptations in social relationships. The number of Indonesians who utilize the internet is steadily increasing. Due to the high mobility of humans, the commercial world places high value on the provision of goods and services and goods on demand and in a timely basis. Consumers now have the option of participating in convenient and cost-effective e-commerce. Numerous e-commerce platforms exist today. The platform is expansive and reaches all populations. The purpose of this research is to examine the relationship between Shopee’s brand awareness, brand association and perceived quality towards Shopee’s customers satisfaction among Indonesian Young-adults both partially and simultaneously. This research explains the findings of research contributing to Aaker and Keller's theory of brand equity. The primary population for this research is young adults aged 15 to 24 years old from throughout Indonesia, with a total of 100 respondents. The analysist tool used in this research is Kendall Tau_b Correlation Test to calculate ordinally ranked-data. The result of the study explained that Shopee’s brand awareness, brand association and perceived quality have a significant effect partially and simultaneously to customers satisfaction. Therefore, the result shows that brand awareness has a moderate and positive relationship, meanwhile brand association and perceived quality has a strong and positive relationship with customers satisfaction. This research 's result may be incorporated into the marketing strategies of companies and interested parties for maintaining and maximizing Brand Awareness, Brand Association, and Perceived Quality in order to have a good significant effect on potential customers, which can lead to Customer Satisfaction.